Segregation and Socialization: Academic Segregation and Citizenship Attitudes of Adolescents in Comparative Perspective? - Dimokritos Kavadias; Kenneth Hemmerechts; Bram Spruyt (Journal of Social Science Education, 2017)
Purpose: There is a tendency to assess educational systems in terms of their efficiency in gaining high scores on cognitive skills. Schools perform, however, also a socializing function. The whole policy debate tends to ignore the impact of educational systems on attitudes or democratic values. This contribution focuses on the impact of the organization of education in European societies on the civic attitudes of adolescents.